2021
DOI: 10.3897/silvabalcanica.22.e58020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tree diameter distributions in managed and unmanaged Kazdağı fir forests

Abstract: Forest structural complexity affects tree growth, species diversity, understory seedling density, wildlife habitat and fire behaviour. Thus, defining the structural complexity of forest ecosystems would play a crucial role in their management. The vertical structure in stands of shade-tolerant tree species can be described by using the distribution of tree diameters. In this study, the main objective was to determine and compare the diameter distribution patterns of managed and unmanaged Kazdağ&#3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…In this study, the tree ring width was almost 1.5 times higher in managed stands than in unmanaged stands. The previous studies also well agreed with the current findings of this study (Mausolf et al, 2018;Kara, 2021). In this study, it can be suggested that forest management had a positive influence on the radial growth of Scots pine and Sessile oak trees in managed forests and also we can assume that managed forests could exhibit more adaptive trees to environmental stressors than in unmanaged forests.…”
Section: Scots Pinesupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the tree ring width was almost 1.5 times higher in managed stands than in unmanaged stands. The previous studies also well agreed with the current findings of this study (Mausolf et al, 2018;Kara, 2021). In this study, it can be suggested that forest management had a positive influence on the radial growth of Scots pine and Sessile oak trees in managed forests and also we can assume that managed forests could exhibit more adaptive trees to environmental stressors than in unmanaged forests.…”
Section: Scots Pinesupporting
confidence: 92%
“…In this study, we can assume that trees grown in unmanaged forests can be more susceptible to windstorms, icing, and snow damage than in managed forests. Ecologically, managed forests ensure sustainable productivity and health of the forest ecosystem and also increase the biodiversity of trees (Keenan, 2015;Campetella et al, 2016;Picchio et al, 2018;Latterini et al, 2023). Managed forests are generally better designed for the influence of natural disasters and climate change adaptation thus forests with good silvicultural treatments exhibit high long-term stability and vulnerability to environmental stressors.…”
Section: Scots Pinementioning
confidence: 99%
See 1 more Smart Citation
“…Nilai agglomerative coefficient merupakan ukuran struktur pengelompokkan dan struktur pengelompokkan yang paling kuat akan terpilih (Kara, 2021). Struktur pengelompokkan aglomeratif ini akan semakin kuat apabila nilai koefisiennya mendekati satu.…”
Section: Metode Nilaiunclassified
“…However, fire suppression in fire-adapted ecosystems often leads to changes in the forest fuel bed, and such changes may promote more are typical of old-growth forests, where tree competition often creates bimodal diameter distributions, and differentiates the stand into social cohorts . In the study of Kara (2021) forest, characterized by a potential fire regime of frequent and low-severity fires .…”
Section: Discussionmentioning
confidence: 99%